The construction of white-light-emitting anisotropic hydrogel. (May 2023) - Yu, Guizhen; Niu, Qingyu; Liu, Xiao; He, Liang; Yu, Jinxie; Han, Hang; Wang, Wenjing; Zhang, Ying; Li, Zhiqiang; Xiong, Qingqing
Abstract: In this work, hybrid anisotropic hydrogel is developed through dispersing carbon quantum dots, ultrahigh magnetic nanoparticle-coated alumina (Fe/Al2 O3 ) platelets in acrylamide aqueous solution in the assistance of magnetic field, then fix the oriented structure via gelation. The aligned Fe/Al2 O3 platelets result in formation of anisotropic structure, thus endows the hydrogels mechanical anisotropy and fluorescent anisotropy. White-light emission is obtained via varying the weight ratio of yellow-emitting ZnO QDs and blue-emitting N, S-CDs. This strategy not only enriches the mechanical/fluorescent dual anisotropic soft materials, but also have great potential application in the fields of organic light-emitting diodes, nonlinear optics and field effect transistors. Highlights: Anisotropic fluorescent hydrogel is prepared via alignment of Fe/Al2 O3 platelets. The orientation-dependent shading effect endows anisotropic fluorescent properties. White-light-emitting is achieved through adjusting the ratio of the two fluorescent emitters.